Modulating Crystallinity of Graphitic Carbon Nitride for Photocatalytic Oxidation of Alcohols. Issue 22 (4th October 2017) - Zhou, Min; Yang, Pengju; Yuan, Rusheng; Asiri, Abdullah M.; Wakeel, Muhammad; Wang, Xinchen
Abstract: Exploiting efficient photocatalysts with strengthened structure for solar‐driven alcohol oxidation is of great significance. The photocatalytic performance of graphitic carbon nitrides can be considerably promoted by modulating its crystallinity. Results confirmed that a high crystallinity accelerates the separation and transfer of photogenerated charge carriers, thus providing more free charges for photoredox reactions. More importantly, the high crystallinity facilitated the adsorption of benzyl alcohol and desorption of benzaldehyde and simultaneously lowered the energy barrier for O2 activation. As a result, the crystalline carbon nitride exhibited a roughly twelvefold promotion with respect to the normal carbon nitride. The remarkable enhancement of activity can be attributed to the synergistic effects of increased electron–hole separation and increased surface reaction kinetics. These findings will open up new opportunities to modulate the structure of polymers for a wide variety of organic reactions. Abstract : Crystals illuminated : Modulating crystallinity of graphitic carbon nitrides can dramatically enhance the separation of photogenerated charges and reaction kinetics, which gives rise to high photocatalytic activity for alcohol oxidation.